Experimental Investigation of Concrete Using Polypropylene As An Admixture : A Review - Quamrul Islam; Harish Nema; Ravindra Gautam (International Journal of Scientific Research in Civil Engineering, 2022)
A composite material that consists essentially of a binding medium, such as a mixture of Portland cement and water, within which are embedded particles or fragments, usually a combination of fine and coarse aggregate. The tensile strength of concrete is much lower than its compressive strength, it is typically reinforced with steel bars; reinforced concrete. Concrete has better resistance in compression while steel has more resistance in tension. Conventional concrete has limited ductility, low impact and abrasion resistance and little resistance to cracking. Good concrete must possess high strength and low permeability. Hence, alternative Composite materials are gaining popularity because of ductility and strain hardening. To improve the post-cracking behaviour, short discontinuous and discrete fibres are added to the plain concrete. The addition of fibres improves the post-peak ductility performance, pre-crack tensile strength, fracture strength, toughness, impact resistance, flexural strength resistance, fatigue performance etc. The ductility of fibre-reinforced concrete depends on the ability of the fibres to bridge cracks at high levels of strain.